A STUDY ON THE PERFORMANCE OF E-BANKING AND ITS CUSTOMER PERCEPTION (International Journal of Food and Nutritional Sciences, 2022)
Purpose: The purpose of the study the performance of E-banking and its perception of the customersTheoretical framework: TAM model has been used as a theory which can be applicable in case of E-banking performanceDesign/Methodology/Approach: The primary quantitative method has been and survey procedure has been conducted. Collected responses has been analyzed through graphical representationFindings: It has been identified that E-banking can make the banking activities easier from the customers. AI and cloud computing can be used to improve the services of E-banking. Research, practical work, and social implication: The study helps to highlight the importance of E-bankingOriginality/ Value: The value of the study is that it gives a better understanding about the performance of E-banking and customer perception